Optimized Treatment of Refractory Hypercholesterolemia in Patients With Atherosclerotic Cardiovascular Disease or Heterozygous Familial Hypercholesterolemia With Alirocumab (OPTIMIZE) - Sudano, Isabella; Mach, Francois; Moccetti, Tiziano; Burkard, Thilo; Fahe, Christian; Delabays, Alain; Rickli, Hans; Keller, Pierre-Frédéric; Dopheide, Jörn; Bodenmann, Sereina; Fiolka, Tom; Ehret, Georg; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Low-density lipoprotein cholesterol (LDL-C) is a major risk factor for atherosclerotic cardiovascular disease (ASCVD). In confirmatory trials, proprotein convertase subtilisin/kexin type 9 inhibitor alirocumab substantially lowered LDL-C and reduced cardiovascular morbidity and mortality. However, the routine clinical use of alirocumab in Switzerland has not yet been studied. Methods In this prospective nation-wide cohort study, we aimed to investigate the patient profile and routine clinical efficacy and safety of alirocumab in 207 patients with ASCVD or heterozygous familial hypercholesterolemia and increased LDL-C despite maximally tolerated statin therapy. LDL-C was measured at baseline and after 3-months follow-up. Results Overall, mean age was 63 ± 11 years, 138 (67%) were men, and 168 (81%) had statin intolerance (SI). Patients with SI had a higher baseline LDL-C (4.3 ± 1.4 vs. 3.3 ± 1.4 mmol/l; p < 0.001) and less frequently ASCVD (71% vs. 95%; p = 0.002). After 3 months of treatment with alirocumab, LDL-C was reduced from 4.1 ± 1.5 to 2.0 ± 1.2 mmol/l (50.5%; p < 0.001). Mean absolute and relative reductions in LDL-C were similar in patients with vs. without SI (2.2 ± 1.2 vs. 1.9 ± 1.3 mmol/l; p = 0.24 and 49.0 vs. 56.6%; p = 0.11, respectively). In total, adverse events were recorded in 25 (12%) patients, with no new safety signals. Conclusions In routine clinical practice, alirocumab was predominantly used in patients with SI suggesting that the great majority of patients with insufficient LDL-C control who would be candidates for alirocumab are not receiving this therapeutic option in Switzerland. LDL-C lowering was potent and similar in patients with and without SI, replicating the favorable efficacy-safety profile of alirocumab from randomized trials.